Kebijakan Pemerintah Papua dalam Pelestarian Tradisi Bakar Batu - Herningsih Herningsih (Millati: Journal of Islamic Studies and Humanities, 2018)
Papua which is geographically located on the eastern tip of Indonesia is an area which has a wealth of not only very abundant natural resources but also cultural traditions diversity and traditional arts. Every ethnic group in the area that was formerly known as Irian Jaya has typical of each traditional art. In order to preserve other cultural and artistic traditions, according to Law Number 21 Year of 2001 concerning Special Autonomy for the Papua Province, the central government gives authority to the Government of Papua to regulate and preserve themselves within the NKRI (The Unitary State of the Republic of Indonesia) framework, including the authority to empower, conserve and develop traditional arts as the cultural identity of the Papuan people such as the tradition of stone burning carried out by the Komunitas Muslim di Bumi Cendrawasih (moslem community in Papua). This paper discusses the policy of the Government of Papua in preserving the stone burning tradition among muslims, traditional arts and the inhibiting and supporting factors in implementing the policy.